ATTITUDE TO THE PARENTAL FAMILY IN ADOLESCENCE AND THEIR PERSONAL AND MORAL DEVELOPMENT - Gorlova, E. L. (Modern Psychology, 2019)
The development of adolescents is complicated by the transitivity of modern society, destruction of family values and traditions collapse. Our question: how family values are realized in the personal choices of adolescents. Objective: study of the personal development and perceptions of adolescents about the family, comparing with the results of the evaluation of education, and moral development. Hypothesis: the content of ideas about the family is associated with the personal and moral development of adolescents. The attitude of adolescents to the family, the effectiveness of the process of education are investigate. All results are analyzed in detail separately and a correlation analysis of the results is carried out. Family values of adolescents are associated with the quality of the family environment, and attitude to work is correlated with the quality of the educational and cultural environment.
Keywords: adolescences, personal development, values, family relationships.